2007
DOI: 10.1136/vr.161.20.685
|View full text |Cite
|
Sign up to set email alerts
|

Economic cost of difficult calvings in the United Kingdom dairy herd

Abstract: Information on the losses associated with lower milk production and reproductive performance, as well as information from a survey of uk dairy herds using beef semen was used to estimate the economic importance of calving difficulties in uk dairy herds. The survey covered information on cow and calf mortality, cow culling and the need for veterinary assistance, the incidences of which were related to the degree of calving difficulty experienced. The total cost of a slightly difficult calving was estimated to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 4 publications
2
31
0
2
Order By: Relevance
“…Olson et al (2009) reported that gestation length had an unfavourable genetic correlation with both stillbirth and dystocia, as longer gestation intervals produced more dystocia and more stillbirths. The calving difficulty was affected by multiple factors, such as the breed of the sire of calf, age of the dam, sex of the calf and twin calvings and were similar to those reported by McGuirk et al (2007).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Olson et al (2009) reported that gestation length had an unfavourable genetic correlation with both stillbirth and dystocia, as longer gestation intervals produced more dystocia and more stillbirths. The calving difficulty was affected by multiple factors, such as the breed of the sire of calf, age of the dam, sex of the calf and twin calvings and were similar to those reported by McGuirk et al (2007).…”
Section: Discussionsupporting
confidence: 76%
“…The cost of labour and veterinary assistance should be added to this loss. Calf mortality also rises with more difficult calvings, ranging between 2.6% in uneventful calvings and 51.8% in the most difficult calvings (McGuirk et al, 2007). Parity of the dam was a significant source of variation for calving difficulty and was lower when the age was higher.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been estimated that these losses in the dairy industry in the US and the UK amounted to US$ 125 million and £ 60 million, respectively [11] . McGuirk et al [12] . estimated that the total cost attributable to a severe case of calving difficulty can be as high as 500 euros per case.…”
Section: Introductionmentioning
confidence: 99%